Literature Study: Financial Statement Analysis as a Tool for Measuring Corporate Financial Perfomance - Yolanda, Nabila; Khoiri Lutfhi, Muhammad; Delani, Maisya; Panggabean, Fitri Yani (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
This study aims to analyze financial statements as a means of measuring the company's financial performance. Financial statements serve an important function in assessing financial health, operational effectiveness, and efficiency of company management. Through a qualitative approach and literature study method, this research collects data from various journals and previous research on financial measurement tools and ratios. The analysis was conducted using liquidity, solvency, activity, and profitability ratios. The results show that most companies face challenges such as high dependence on debt, inefficiency in asset management, and high operating expenses. However, successful companies usually have good liquidity management and efficient capital management. Recommendations include improving liquidity management, asset utilization efficiency, diversifying funding sources, and controlling operating expenses. In addition, the development of marketing strategies, HR training, and regular monitoring are also suggested to improve financial performance. This study confirms the importance of financial statement analysis in strategic decision-making and evaluating company health. It is hoped that these findings can serve as a reference for practitioners and academics in utilizing financial statements to improve the company's financial performance.